Nitrogen in the Home Landscape - Amy L. Shober; Alexander J. Reisinger (EDIS)
This document helps homeowners understand how N interacts in the environment through the nitrogen cycle, making maintenance of home landscapes or gardens easier and more sustainable. This document is SL 254, one of a series of the Department of Soil, Water, and Ecosystem Sciences, UF/IFAS Extension. Original publication date January 2008. Revised March 2011 and August 2022. https://edis.ifas.ufl.edu/ss479